Research and innovation in agricultural water management for a water-secure world - Smith, Mark; Sikka, Alok; Dirwai, Tinashe Lindel; Mabhaudhi, Tafadzwanashe (Wiley, 2023)
There is increased awareness that the current food system is unsustainable and that transformative research, development and innovation in agricultural water management (AWM) are needed to transform water and food systems under climate change. We provide an overview of research efforts, challenges, opportunities and innovations to improve water resource management and sustainability, especially in the agricultural sector. We highlight how sustainable AWM is central to balancing the needs of a growing population and increasing food demand under increasing water insecurity and scarcity, with environmental and socio-economic outcomes. Innovative technologies are being developed to optimize water use and productivity through sustainable irrigation technologies, irrigation modernization and smart water management. However, these innovations still need to fully address equity, inequality and social justice concerning access to water, infrastructure and the delayed technological advances in the global South. This requires adopting transdisciplinary approaches, as espoused by the water–energy–food (WEF) nexus, to better anticipate and balance trade-offs, optimize synergies and mitigate risks of maladaptation. Through such transdisciplinary approaches, AWM innovations could better consider local socio-economic, governance, institutional and technological constraints, thus allowing for more contextualized and relevant innovations that can be scaled.